The knowledge work factory turning the productivity paradox into value for your business - Heitman, William F. (McGraw Hill-Ascent Audio, 2019)
Unlock your company's true potential by eliminating knowledge work waste that's hiding in plain sight. Back in 1987, Nobel laureate Robert Solow quipped, "You can see the computer age everywhere but in the productivity statistics." This costly condition soon became known as the "productivity paradox." Why does it persist today? Why do knowledge workers spend a third of their days on needless correction, avoidable work and overservice, despite existing office technology that could help, even automate, their actions? And why does nobody notice? The answers-and solutions-are in this book. The Knowledge Work Factory uncovers the well-intentioned waste that hides in plain sight within virtually every organization. It reveals the ingrained perceptual biases that trick our brains into accepting the status quo and missing breakthrough opportunities. It draws stunning parallels to industrial production, which cracked this very code over 100 years ago. Most importantly, it gives you an easy-to-follow, one-stop guide to boost efficiency, productivity, and morale among the very knowledge workers who struggle under the burden of the productivity paradox. Discover your organization's true, untapped capacity. Maximize the productivity of every single knowledge worker. Uncover "better-than-best practices." Reap benefits that drop straight to the bottom line. The power is in your hands-with The Knowledge Work Factory.